Development of problems of medical embryology at the Institute of Experimental Medicine - Puchkov, V. F. (Морфологія / Morphologia / Morfologìâ, 2011)
In 1932, the Decree of the Government of the USSR to the State Institute of Experimental Medicine in Leningrad was granted the status of the All-Union (VIEM) and set new tasks. The institute should begin to comprehensively study the human body on the basis of modern theory and practice of medical sciences in order to find and develop new methods of research, treatment and prevention on the basis of the latest advances in the field of biology, physics and technical reconstruction of special equipment of laboratories and clinics.